THE GEOGRAPHICAL LOCATION, POLITICAL MAP, AND NATURAL RESOURCES OF AFRICA - Shavkatova Dilnoza Iskandar Qizi (PEDAGOGS, 2025)
Abstract. Africa is one of the largest continents in the world, characterized by its vast territory, rich natural resources and complex political structure. The continent is of great importance for the world with its different natural conditions, climatic zones and ethnic diversity.